Mediation Role of Customer Satisfaction in the Influence of Brand Equity and Trust Toward Customer Loyalty - Kamaruzzaman Onaning (Jurnal Ilmu Manajemen Advantage, 2022)
This research was conducted to examine and analyze the mediating role of customer satisfaction in the influence of brand equity and trust on customer loyalty. The method used in this research is Structural Equation Modeling (SEM) using the SmartPLS application. The population in this study are customers of The Great Asia Africa, totaling 196 respondents. Therefore, respondents in this study were customers of The Great Asia Africa, totaling 100 people or approximately half of the customer population of The Great Asia Africa. The author took a sample of 100 respondents following the theory of Frankel and Wallen (1993) which suggests the minimum sample size for descriptive research is 100 people. This research method was carried out using the Descriptive Research Design model with data collection methods using a questionnaire. The test results show that Customer Trust has no significant effect on Customer Loyalty with the intervening variable of Customer Satisfaction, Brand Equity has no significant effect on Customer Loyalty with the intervening variable of Customer Satisfaction, Customer Trust has a positive effect on Customer Loyalty, and Brand Equity has a positive effect on Customer Loyalty.